Identification of a Conserved B-Cell Epitope on Duck Hepatitis A Type 1 Virus VP1 Protein - Wu, Xiaoying (PLoS One, 2015)
BACKGROUND: The VP1 protein of duck hepatitis A virus (DHAV) is a major structural protein that induces neutralizing antibodies in ducks; however, B-cell epitopes on the VP1 protein of duck hepatitis A genotype 1 virus (DHAV-1) have not been characterized. METHODS AND RESULTS: To characterize B-cell epitopes on VP1, we used the monoclonal antibody (mAb) 2D10 against Escherichia coli-expressed VP1 of DHAV-1. In vitro, mAb 2D10 neutralized DHAV-1 virus. By using an array of overlapping 12-mer peptides, we found that mAb 2D10 recognized phages displaying peptides with the consensus motif LPAPTS. Sequence alignment showed that the epitope (173)LPAPTS(178) is highly conserved among the DHAV-1 genotypes. Moreover, the six amino acid peptide LPAPTS was proven to be the minimal unit of the epitope with maximal binding activity to mAb 2D10. DHAV-1–positive duck serum reacted with the epitope in dot blotting assay, revealing the importance of the six amino acids of the epitope for antibody-epitope binding. Competitive inhibition assays of mAb 2D10 binding to synthetic LPAPTS peptides and truncated VP1 protein fragments, detected by Western blotting, also verify that LPAPTS was the VP1 epitope. CONCLUSIONS AND SIGNIFICANCE: We identified LPAPTS as a VP1-specific linear B-cell epitope recognized by the neutralizing mAb 2D10. Our findings have potential applications in the development of diagnostic techniques and epitope-based marker vaccines against DHAV-1.